PERANAN PEREMPUAN PENENUN DALAM MENINGKATKAN PENDAPATAN RUMAH TANGGA - Yuniarti Reny Renggo; Raynesta Mikaela Indri Malo (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
East Sumba is one area known as a woven fabric, where most weavers are women (housewives) (Takandjandji, 2016). The products produced are various types of fabrics, namely Hinggi, which is a traditional men's clothing in the form of long cloth, lawu or sarong which is a traditional garment for women, and also a scarf worn by men and women by means of shoulder bagging. Analysis of the role of using Mosser's work consists of 3 roles (productive, reproductive, and social), where women have a large role in increasing family income. The role is inseparable from the control of men (husbands). The ikat weaving business is very helpful in improving the household economy